Becoming an entrepreneur in the Metropole: resisting incubators’ recolonizing attempts - Severine Le Loarne Lemaire; Gloria Haddad; Rola Al Ali; Gaël Bertrand (Cadernos EBAPE.BR)
Abstract This study investigates the decolonization process among nascent entrepreneurs from formerly colonized nations, operating within underprivileged areas of developed countries. Through a two-year ethnographic inquiry involving entrepreneurs from former French African Colonies and Departments conducting business in the Metropole, the paper recounts their journey from being subject to attempts at recolonization to achieving decolonization. Using colonialist theory and the approach of entrepreneurship as a practice, it explores how entrepreneurs resisted efforts by incubators to impose colonial ideologies, ultimately embracing their own entrepreneurial practices. Three distinct decolonization processes emerge from this analysis. This paper contributes to colonialist theory in three key ways. Firstly, it proposes a methodological framework for identifying signs of colonialism and decolonization through the observation of entrepreneurial practices. Secondly, it extends the applicability of colonialist theory beyond traditional Global South contexts, demonstrating its relevance within immigrant communities from former colonies. Lastly, it clarifies the concept of decolonization, emphasizing the adoption of entrepreneurial practices reflective of individual choice and agency rather than mere rejection of colonialist norms.